Correlates of aortic stiffness in elderly individuals: a subgroup of the Cardiovascular Health Study. - Mackey, Rachel H; Sutton-Tyrrell, Kim; Vaitkevicius, Peter V; Sakkinen, Pamela A; Lyles, Mary F; Spurgeon, Harold A; Lakatta, Edward G; Kuller, Lewis H (Am J Hypertens, 2002)
BACKGROUND: Arterial stiffness has been associated with aging, hypertension, and diabetes; however, little data has been published examining risk factors associated with arterial stiffness in elderly individuals. METHODS: Longitudinal associations were made between aortic stiffness and risk factors measured approximately 4 years earlier. Aortic pulse wave velocity (PWV), an established index of arterial stiffness, was measured in 356 participants (53.4% women, 25.3% African American), aged 70 to 96 years, from the Pittsburgh site of the Cardiovascular Health Study during 1996 to 1998. RESULTS: Mean aortic pulse wave velocity (850 cm/sec, range 365 to 1863) did not differ by ethnicity or sex. Increased aortic stiffness was positively associated with higher systolic blood pressure (SBP), age, fasting and 2-h postload glucose, fasting and 2-h insulin, triglycerides, waist circumference, body mass index, truncal fat, decreased physical activity, heart rate, and common carotid artery wall thickness (P < .05). After controlling for age and SBP, the strongest predictors of aortic stiffness in men were heart rate (P = .001) and 2-h glucose (P = .063). In women, PWV was positively associated with heart rate (P = .018), use of antihypertensive medication (P = .035), waist circumference (P = .030), and triglycerides (P = .081), and was negatively associated with physical activity (P = .111). Results were similar when the analysis was repeated in nondiabetic individuals and in those free of clinical or subclinical cardiovascular disease in 1992 to 1993. CONCLUSIONS: In these elderly participants, aortic stiffness was positively associated with risk factors associated with the insulin resistance syndrome, increased common carotid intima-media thickness, heart rate, and decreased physical activity measured several years earlier.
Keywords: Aged; Aged, 80 and over; Aging; Aorta; Female; Heart Rate; Humans; Hypertension; Insulin Resistance; Longitudinal Studies; Male; Pulsatile Flow; Risk Factors; Sex Distribution